The Influence of Indonesian Development Index to Modernization Level of 38 Indonesian Provinces in 2023 - Renny Candradewi Puspitarini Puspitarini; Nuril Hidayati; Tri Nanda (Journal of Public Administration and Local Governance, 2025)
This study examines the relationship between modernization level and the human development index using linear regression on 34 observations. The findings reveal a highly significant and robust positive correlation: modernization level accounts for nearly 89% of the variation in the human development index (R square = 0.8881). A one-unit increase in modernization level is associated with an approximate 3.54-unit rise in the human development index (coeff. = 3.543167, p < 0.001), with a 95% confidence interval of [2.895228, 4.191105]. The overall model is highly significant (F(1, 32) = 124.07, p < 0.001), confirming modernization's strong predictive power. Theoretically, these results strongly support modernization theories, affirming that societal modernization directly and substantially improves human well-being, encompassing health, education, and living standards. The high R2 suggests modernization is a primary driver of human development. Practically, these findings have significant implications for policymakers, particularly in Indonesia. Given the strong positive link, accelerating modernization through investments in infrastructure, education, technology, and economic diversification will likely yield substantial gains in human development. Policies promoting industrialization, technological adoption, and improved access to education and healthcare should be prioritized as direct pathways to achieving higher human development indices